Bedford and the Structure of Section 7 - Stewart, Hamish (McGill Law Journal, 2015)
In Canada (A.G.) v. Bedford, the Supreme Court of Canada invalidated three prostitution-related provisions of the Criminal Code on grounds of overbreadth and gross disproportionality. The implications of Bedford go well beyond the particular context of sex work and even of criminal law. First, the Court held that the three constitutional norms against overbreadth, arbitrariness, and gross disproportionality are distinct from each other rather than aspects of a single norm against overbreadth. Second, the Court held that a Charter applicant could establish a violation of section 7 by showing that a law is overbroad, arbitrary, or grossly disproportionate in its impact on the life, liberty, or security of only one person and that the effectiveness of the law in achieving its policy objectives was not relevant to these norms. There are some difficulties in understanding this highly individualistic approach to section 7, and those difficulties lead to the third implication. By deferring any consideration of the effectiveness of the law to the question of whether it is a proportional limit on a section 7 right, the Court may be indicating a willingness to do something it has never done before: recognize an infringement of a section 7 right as a justified limit under section 1. The Court’s clarification of the relationship between the norms against overbreadth, arbitrariness, and gross disproportionality is welcome, but its individualistic articulation of those norms is difficult to understand and its suggestion that section 7 violations may now be easier to save under section 1 is troubling.